A NEW HOUSE IS THE FULFILLMENT OF NEW DREAMS AND HOPES (Proceedings of International Educators Conference, 2023)
In our country, great attention is paid to the provision of housing to the population, for this purpose, to the construction of multi-storey buildings that fully meet the requirements of the times. Of course, the construction of low-income housing for families with many children and people with disabilities is not excluded.